PERAMALAN PENJUALAN MAKANAN RINGAN DENGAN METODE SINGLE EXPONENTIAL SMOOTHING - Mukti Qamal (Teknik Informatika Universitas Malikussaleh, 2019)
The developments of information technology urge companies to escalate their performance, effectiveness and eficiency. One of the important information technology application is prediction. For a distributor or a retailer, the capability of predicting the selling is notable to determine an accurate stock of goods. This matter avoids a shortage of the stock of some items in a store and help them to operate warehouse efficiently. In this research, a prediction of selling quantity of a snack distributor is carried out using single exponential smoothing method. The research shows that by using a single exponential smoothing to predict the selling can help the business entity to maintain the availability of goods and improve their performance in managing the storehouse, even though the accuracy of this method in the prediction is not too good.